Artificial Intelligence Research - Kongratbay, Tlemisov Ilham; Faxratdinovich, Jangabaev Muxtar; Ayxoja uli, Janxojaev Asqar; Òserbay uli, Qallibekov U’mitbek (European Journal of Life Safety and Stability (2660-9630), 2023)
This article presents data on artificial intelligence and its application in industry.